2018
DOI: 10.1113/jp275406
|View full text |Cite
|
Sign up to set email alerts
|

A role for focal adhesion kinase in facilitating the contractile responses of murine gastric fundus smooth muscles

Abstract: Smooth muscle contraction involves regulating myosin light chain phosphorylation and dephosphorylation by myosin light chain kinase and myosin light chain phosphatase. C-kinase potentiated protein phosphatase-1 inhibitor of 17 kDa (CPI-17) and myosin phosphatase targeting subunit of myosin light-chain phosphatase (MYPT1) are crucial for regulating gastrointestinal smooth muscle contraction by inhibiting myosin light chain phosphatase. Integrin signalling involves the dynamic recruitment of several proteins, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…2015; Xie et al . 2018). Recently we demonstrated that membrane cholesterol and substrate stiffness coordinate to induce the remodelling of the cytoskeleton and alter the biomechanics of VSMCs (Sanyour et al .…”
Section: Introductionmentioning
confidence: 99%
“…2015; Xie et al . 2018). Recently we demonstrated that membrane cholesterol and substrate stiffness coordinate to induce the remodelling of the cytoskeleton and alter the biomechanics of VSMCs (Sanyour et al .…”
Section: Introductionmentioning
confidence: 99%
“…We previously found that PF-431396 inhibits the increase in CPI-17 T38 phosphorylation during EFS-evoked cholinergic contractions [21]. Because FAK is recruited to β1integrin in focal adhesions, we examined whether CPI-17 is also recruited and phosphorylated at focal adhesions.…”
Section: Effects Of Cholinergic Stimulation and Pf-431396 On β1integrmentioning
confidence: 96%
“…Gastric fundus smooth muscles were obtained by sharp dissection as described [21]. Each sheet of fundus smooth muscles was pinned out flat, cut into a rectangle of 10mm × 15mm, and then folded, in parallel with the circular muscles, into a rectangle of 10mm × 5mm.…”
Section: Contractile Responsesmentioning
confidence: 99%
See 2 more Smart Citations